2021
DOI: 10.12688/openreseurope.13241.3
|View full text |Cite
|
Sign up to set email alerts
|

Improving the touchscreen-based food approach-avoidance task: remediated block-order effects and initial findings regarding validity

Abstract: Approach biases to foods may explain why food consumption often diverges from deliberate dietary intentions. Yet, the assessment of behavioural biases with the approach-avoidance tasks (AAT) is often unreliable and validity is partially unclear. The present study continues a series of studies that develop a task based on naturalistic approach and avoidance movements on a touchscreen (hand-AAT). In the hand-AAT, participants are instructed to respond based on the food/non-food distinction, thereby ensuring atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
0
10
2
Order By: Relevance
“…On the other hand, when block order is counterbalanced, it can generate spurious interpersonal differences in approach-avoidance bias, suppressing correlational effects and creating spuriously high reliability. In fact, some studies suggest that participants respond faster due to training effects in the second block (Galler et al, 2022;Kahveci et al, 2021;Wittekind et al, 2021), while no order effects were found in other studies (Krieglmeyer & Deutsch, 2010;Rougier et al, 2018;van Alebeek et al, 2021).…”
Section: Aat Instructionsmentioning
confidence: 94%
“…On the other hand, when block order is counterbalanced, it can generate spurious interpersonal differences in approach-avoidance bias, suppressing correlational effects and creating spuriously high reliability. In fact, some studies suggest that participants respond faster due to training effects in the second block (Galler et al, 2022;Kahveci et al, 2021;Wittekind et al, 2021), while no order effects were found in other studies (Krieglmeyer & Deutsch, 2010;Rougier et al, 2018;van Alebeek et al, 2021).…”
Section: Aat Instructionsmentioning
confidence: 94%
“…Finally, a strong approach bias in combination with low inhibitory control resulted in elevated snack consumption (Kakoschke et al, 2015). The probably more reliable feature-relevant food AAT revealed positive associations of a food-approach bias with food craving, external eating, food liking, and desire to eat (Kahveci et al, 2020;van Alebeek et al, 2021).…”
Section: Approach-avoidance Taskmentioning
confidence: 95%
“…In the AAT, participants respond with pull-(approach) or push-(avoidance) movements (e.g., via computer mouse, joystick, or touchscreen) to stimuli from different categories (e.g., food and non-food; see, e.g., van Alebeek et al, 2021). Shorter reaction times of approach than of avoidance responses to stimuli of the category of interest (and this to a larger extent than to the stimuli of another category) are interpreted as an approach bias.…”
Section: Approach-avoidance Taskmentioning
confidence: 99%
See 2 more Smart Citations